Mammographic detection of breast arterial calcification as an independent predictor of coronary atherosclerotic disease in a single ethnic cohort of African American women - Newallo, Domnique; Baumann, Stefan (Atherosclerosis, 2015)
Objective: Accumulating data on predominantly Caucasian women suggests an association between breast arterial calcification (BAC) and coronary artery disease (CAD). We sought to comprehensively examine the correlation between mammographic BAC and CAD endpoints detected by cardiac computed tomography (CCT) in African American (AA) women. Methods: Consecutive AA women who underwent digital screening mammography and CCT were identified. In blinded fashion, mammographic and CCT studies were reviewed. Patient-related pertinent covariates were assessed. Results: Two-hundred-four AA women (median age, 52.5 years) were included. BAC was present in 42 women (20.6%). BAC was significantly associated with coronary artery calcium score >100 (odds ratio [OR], 7.66; 95% confidence interval [CI], 2.75-21.29; P < 0.001), atherosclerotic luminal narrowing (OR, 9.99; CI, 3.65-27.32; P < 0.001), and stenosis ≥50% (OR, 5.48; CI, 1.97-15.23; P = 0.001) by CCT. Conclusion: In AA women, BAC is associated with increased probability of coronary calcification, atherosclerosis, and CAD on CCT.